Using athletes` world rankings to assess countries' performance - Malcata, R. M.; Vandenbogaerde, T. J.; Hopkins, W. G. (International Journal of Sports Physiology and Performance, 2014)
There is a need for fair measures of country sport performance that include athletes who do not win medals. Purpose: To develop a measure of country performance based on athlete ranks in the sport of swimming. Methods: Annual top-150 ranks in Olympic pool-swimming events were downloaded for 1990 through 2011. For each athlete of a given rank, a score representing the athlete`s performance potential was estimated as the proportion of athletes of that rank who ever achieved top rank. A country`s scores were calculated by summing its athletes` scores over all 32 events. Reliability and convergent validity were assessed via year-to-year correlations and correlations with medal counts at major competitions. The method was also applied to ranks at the 2012 Olympics to evaluate countries` swimming performance. Results: The performance score of an athlete of a given rank was closely approximated by 1/rank. This simpler score has 1 practical interpretation: An athlete ranked 7th (for example) has a chance of 1/7 of ever achieving top rank; for purposes of evaluating country performance, 7 such athletes are equivalent to 1 athlete of the top rank. Country scores obtained by summing 1/rank of the country`s athletes had high reliability and validity. This approach produced scores for 168 countries at the Olympics, whereas only 17 countries won medals. Conclusions: The authors used the sport of swimming to develop a fair and inclusive measure representing a country`s performance potential. This measure should be suitable for assessing countries in any sports with world rankings or with athletes at major competitions.